Comparison of the Safety and Efficacy of Remimazolam Besylate versus Dexmedetomidine for Patients Undergoing Fiberoptic Bronchoscopy: A Prospective, Randomized Controlled Trial - Xu H; Wang L; Zhu W; Ren C; Liu G; Liu Y (Dove Medical Press, 2024)
Huiying Xu,1 Lizhen Wang,2 Wenchao Zhu,1 Chunguang Ren,1 Guoying Liu,1 Yanchao Liu1 1Department of Anaesthesiology, Liaocheng People's Hospital, Liaocheng, People's Republic of China; 2Department of Tuberculosis, Liaocheng Infectious Disease Hospital, Liaocheng, People's Republic of ChinaCorrespondence: Yanchao Liu, Email lycxyl9@sina.comObjective: Remimazolam besylate is a novel ultra-short-acting benzodiazepine that is rapidly hydrolyzed to zolpidem propionic acid by tissue lipases. We designed this study to compare the safety and efficacy of remimazolam besylate alfentanil versus dexmedetomidine-alfentanil for fiberoptic bronchoscopy (FB).Methods: One hundred and twenty patients undergoing FB into this prospective randomized controlled trial were divided into two groups. The anesthesia induction consisted of 6 mg/kg/h of remimazolam besylate in the RA group and 0.5 μg/kg of dexmedetomidine in the DA group. 1- 2 mg/kg/h of remimazolam besylate or 0.2- 0.7 μg/kg/h of dexmedetomidine were administered to maintain during FB. The lowest oxygen saturation, success rate of FB, hemodynamics, time metrics, bronchoscopy feasibility, drug dose requirements, patient and bronchoscopist satisfaction scores, occurrence of intraoperative awareness, number of patients willing to repeat FB with the same sedation regimen, and occurrence and severity of adverse events.Results: The lowest oxygen saturation during the FB was significantly higher in the RA group (P = 0.001). Compared with the variables in the DA group, peripheral oxygen saturation, systolic blood pressure, and diastolic blood pressure were significantly lower at T2 and T3 in the RA group (P < 0.05). Heart rates were significantly higher from T2 to T4 in the DA group (P < 0.05). More patients experienced bradycardia in the DA group (P = 0.041). Compared with time metrics in the DA group, the induction time, fully-alert time, and recovery room-leaving time were all significantly shorter in the RA group (P < 0.05). The bronchoscopy feasibility scores in the RA group were significantly lower at T2, whereas they were lower at T3 in the DA group (P < 0.05).Conclusion: Remimazolam besylate is superior to dexmedetomidine when combined with alfentanil during FB, promoting faster patients' recovery, better operative conditions and respiratory stability with similar rates of occurrence and severity of adverse events.Keywords: remimazolam besylate, dexmedetomidine, fiberoptic bronchoscopy, alfentanil, propofol